2018
DOI: 10.3390/en11010073
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic and Environmental Analysis of Scaling up Cogeneration Units Driven by Sugarcane Biomass to Enhance Power Exports

Abstract: When manual harvesting of sugarcane was discontinued in many regions of Brazil, interest in power generation by burning the bagasse and straw in cogeneration units rose. Exergy analysis is often applied to increase the thermodynamic yield of these plants by identifying irreversibility and work availability. Conversely, pressure for adopting clean energy requires these systems to be evaluated for suitable environmental performance. This study identified and discussed the thermodynamic and environmental effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 47 publications
0
18
0
1
Order By: Relevance
“…Although different types of fuel can be used in the process (i.e., wood, crop residues from rice, soy, and corn, or even urban and industrial waste), about 80% of the biomass consumed in Brazil for energy purposes is derived from bagasse and straw of sugarcane [27]. Boiler-turbine assemblies that operate according to the Rankine or Brayton cycles and produce steam at 65 bar and 550 • C have been extensively applied in electricity exports [23, [26][27][28].…”
Section: Current Overview Of the Brazilian Gridmentioning
confidence: 99%
See 1 more Smart Citation
“…Although different types of fuel can be used in the process (i.e., wood, crop residues from rice, soy, and corn, or even urban and industrial waste), about 80% of the biomass consumed in Brazil for energy purposes is derived from bagasse and straw of sugarcane [27]. Boiler-turbine assemblies that operate according to the Rankine or Brayton cycles and produce steam at 65 bar and 550 • C have been extensively applied in electricity exports [23, [26][27][28].…”
Section: Current Overview Of the Brazilian Gridmentioning
confidence: 99%
“…All these assemblies have been sufficiently modified to depict the local operating conditions of these sources. For Biomass, the LCI "Electricity, bagasse, sugarcane, at fermentation plant/BR U" used in this study was adapted from premises established by Guerra et al [28].…”
Section: Environmental Assessmentmentioning
confidence: 99%
“…Sugarcane tops could be used for soil improvement since they have higher nutrition, moisture, and degradation rate compared to the dry leaves. Also, the use of 50% sugarcane trash available in the field for cogeneration could help to double the electricity export from the sugar factory [18]. As well, partial removal of the dry leaves would support the sugarcane yield [19].…”
Section: Introductionmentioning
confidence: 99%
“…Nguyen and Hermansen (2014) conducted an LCA study of all processing steps (cultivation, collection and pre-process and thermochemical conversion to electricity) of miscanthus gasification for electricity and heat production [29]. Guerra et al (2017) identified the thermodynamic and environmental effects of scaling up existing cogeneration units in order to use sugarcane biomass as fuel via a plant LCA [30].…”
mentioning
confidence: 99%